Protective effects and mechanisms of cynaroside on renal fibrosis in mice with unilateral ureteral obstruction - Ah Young Yang; Jung-Yeon Kim; Mi-Gyeong Gwon; Kiryeong Kim; Hyun Hee Kwon; Jaechan Leem; Sung-Woo Kim (Redox Report)
Renal fibrosis is a key factor in the progression of chronic kidney disease (CKD), and current treatments remain inadequate. In this study, we investigated the therapeutic effects of cynaroside (Cyn), a natural flavonoid, in a mouse model of renal fibrosis induced by unilateral ureteral obstruction. Cyn treatment significantly ameliorated tubular injury and interstitial fibrosis while improving renal function. Mechanistically, Cyn inhibited the expression of fibrosis-related proteins and suppressed Smad2/3 phosphorylation. Additionally, Cyn reduced myofibroblast accumulation by inhibiting epithelial–mesenchymal transition, as indicated by increased E-cadherin expression and decreased levels of mesenchymal markers. Cyn also reduced oxidative stress by downregulating the prooxidant enzyme NADPH oxidase 4 and restoring antioxidant enzymes. Furthermore, Cyn attenuated ferroptosis by regulating key proteins, including acyl-CoA synthetase long-chain family member 4, transferrin receptor 1, and glutathione peroxidase 4, while also restoring glutathione levels. Cyn alleviated endoplasmic reticulum stress, as evidenced by the downregulation of key markers such as glucose-regulated protein 78 and activating transcription factor 6, and reduced inflammation, as confirmed by decreased macrophage infiltration and lower cytokine production. Overall, Cyn demonstrated broad protective effects against renal fibrosis by modulating oxidative stress, ferroptosis, ER stress, and inflammation, positioning it as a potential therapeutic agent for CKD management.